Evaluation of Persian thesauri of basic sciences based on ANSI / NISO 39.19-2005 standard - Hariri, Nadjla; Maryam, Kazerani; Moghaddam-Kiya, Reza; Hariri, Nadjla; Kazerani, Maryam; Moghaddam-Kiya, Reza (Malaysian Journal of Library and Information Science, 2017)
Hariri, N., Kazerani, M., & Moghaddam-Kiya, R. (2013). Evaluation of Persian thesauri of basic sciences based on ANSI/NISO 39.19-2005 standard. Malaysian Journal of Library & Information Science, Vol.18, no. 1: 55-65. Thesauri have played a significant role as information storage and retrieval aid. However, to ensure effective retrieval of information, thesauri should comply with the standards such as ANSI /NISO Z 39.19 -2005, which provide rules and principles for constructing controlled vocabularies. These rules include four dimensions; form construction, semantic relationships, displaying controlled vocabularies, and management systems. These dimensions served as a basis in this study to evaluate the accuracy of vocabulary construction in four Persian Thesauri of Basic Sciences. The research approach utilised in this study was the analytical survey method and a checklist was developed as the research instrument. The samples of terms established by using Morgan’s table were entered into the checklist and were evaluated on the basis of the relevant standards. According to the results, the thesauri under study had observed the standards of form construction and semantic relationships properly but had not given due attention to management and displaying dimensions.